Takashi Arima and his Transcendentalism - Rana, Pradeep S. (Management Dynamics, 2018)
This study is an enquiry into how self-realization and Transcendentalism in Arima’s poetry diverges from those of the representative Western creative writers. It also explores and identifies effectiveness of rhetorical strategy in Arima’s poetry, examines his method of self-realization through poetry writing, seclusion, and communion with the ‘Super-soul’ in relation to the Western practices. Data for the study were collected by means of structured questionnaires, FGD, books, journals, and online database. The study concludes that Arima’s poetry reads so close to the Western poetry, and yet they are so far apart when it gets down to the real nitty-gritty of Transcendentalism and self-realization as received in the West.